Molecular detection of Cytauxzoon spp. in asymptomatic Brazilian wild captive felids - Andre, Marcos R. [UNESP]; Adania, Cristina H.; Machado, Rosangela Z. [UNESP]; Allegretti, Silmara M.; Felippe, Paulo A. N.; Silva, Ketty F. [UNESP]; Nakaghi, Andrea C. H. [UNESP]; Dagnone, Ana S. [UNESP] (Wildlife Disease Assoc, Inc, 2009)
Cytauxzoon. spp. DNA was detected for the first time in blood samples from asymptomatic Brazilian wild captive felids. In 2606, 72 EDTA blood samples from seven wild felids species: Puma concolor (pinna), Leopardus pardalis (ocelot), Puma yagouaroundi (jaguarundi), Leopardus wiedii (margay), Leopardus tigrinus (little spotted cat), Oncifelis colocolo (pampas cat) and Panthera. onca. (jaguar) were analyzed using polymerase chain reaction to amplify the 18S rRNA gene segment in order to verify the presence of Cytauxzoon spp. DNA. Nine samples were positive: six ocelots, two pumas, and one jaguar. In Brazil, wild felids may be natural reservoirs for Cytauxzoon spp.
Keywords: Brazil; Cytauxzoon spp.; PCR; wild felids